Subjective employee experience of hotel employees in the Junin region - Paredes-Perez, Marco A. J. (2022)
Objective: To determine the characteristics of the employee experience in employees of hotel establishments in the Junín region. Methods. The type of research was basic, descriptive level, simple descriptive design and non-experimental-transectional. The methods used were observation, analysis and synthesis and inductive-deductive, while the instrument applied was the questionnaire and the technique was the survey. The sample consisted of 320 employees of hotel establishments in the Junín region and the sample selection criterion was non-probabilistic by convenience. Results. The main results were that the levels of employee experience at the subjective level were regular in its physical and technological dimensions, and high in its cultural dimension; which reflects that, despite the adverse conditions due to the covid-19 pandemic, the collaborators performed their tasks with appropriateness and assertiveness. Conclusion. Companies in the hotel sector should implement programs that reinforce and establish the objective conditions of their work environment in order to generate profitable and positive subjective experiences in favor of their employees and the productivity of the organization.